Pengaruh Lingkungan Keluarga terhadap Penyalahgunaan NAPZA pada Remaja - Dwi Oktavia Sri Asmoro; Soenarnatalina Melaniani (Universitas Airlangga, 2016)
The number of drug users was increasing. Drug abuse is regarded as one. Drug user regarded as a threat that sooner or later can destroy the young generation. The research was aimed to analized the infl uence of family environmental factors toward to abuse juvenile drug in Surabaya. The research was observational research by design cross sectional. Technique sampling was simple random sampling, with sampling teenager was 10-19 year drug users who performs outpatient in BNN throughout Surabaya as many as 53 people. The study was done at December 2015. This research used obtained through primary and secondary data, the analysis used binary regression logistic techniques. The study results show that the infl uence of family environment that is harmonious family (pvalue = 0,026; or = 6,179), bustle parents (pvalue = 0,032; or = 5,677), parents permissive (p = 0.015; or = 8,001 ), Religious in the family (pvalue = much as 0.021; or = 6,401) and religious in the family are the infl uence on the environment factors (pvalue = 0.021; or = 6,401; CI = 1,321 – 31,025). Religious in the family are the most influence in the family environment factors. It was recommended parents need to create family bonds strong via relationship emotional and taste emphatic on child.